2002
DOI: 10.1080/13691050110095559
|View full text |Cite
|
Sign up to set email alerts
|

Spousal communication on reproductive illness among rural women in southern India

Abstract: Successful inter-spousal communication is promoted as a key strategy to fostering shared decision making and responsibilities on reproductive health matters. With data from a largescale study examining the risk factors of reproductive tract infections (RTIs) in married women, we investigated the extent of inter-spousal communication about reproductive illnesses and its in¯uence on preventive and curative behaviours among 432 symptomatic women and 256 symptomatic men. Data derive from a cross-sectional ®eld inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…So, the communication between husband and wife plays a significant role. It is for determining the reproductive preference, health issues because a successful inter-spousal communication between husband and wife is a key strategy to decision-making and responsibilities on sexual health matters by spouses (Santhya & Dasvarma 2002). In such environment, even when women are educated and motivated to practice reproductive health and family planning services they may have little control over this kind of decision making if their husband neglect to services.…”
Section: Introductionmentioning
confidence: 99%
“…So, the communication between husband and wife plays a significant role. It is for determining the reproductive preference, health issues because a successful inter-spousal communication between husband and wife is a key strategy to decision-making and responsibilities on sexual health matters by spouses (Santhya & Dasvarma 2002). In such environment, even when women are educated and motivated to practice reproductive health and family planning services they may have little control over this kind of decision making if their husband neglect to services.…”
Section: Introductionmentioning
confidence: 99%
“…One approach may be to encourage healthcare providers to discuss with individuals their own and their partner's sexual behaviours and be pro-active about HIV and STD testing and counselling. Research has documented the high levels of sexual and reproductive tract infections (RTIs) in India (Mehendale et al 1996) as well as barriers to diagnosis and treatment (Barua andKurz 2001, Santhya andDasvarma 2002) Similarly, we found that both women and men were loath to discuss such problems with spouses or with doctors. Additionally, research suggests that not all healthcare providers clearly communicate the sexual nature of diagnosed RTIs, recommend partner notification and treatment, or discuss risk reduction methods.…”
Section: Implications and Conclusionmentioning
confidence: 72%
“…Communication between spouses is also explored in a paper from South India which explores issues concerning RTIs in one rural area of Tamil Nadu (Santhya and Dasvarma 2002). Although many previous studies on this topic have examined spousal communication in the ®eld of family planning (Lasee andBecker 1997, Mahmood andRingheim 1997), this paper is one of the few to look at communication about reproductive illness and RTIs, speci®cally.…”
Section: Sexual Health and Sexuality In South And Southeast Asiað Culmentioning
confidence: 95%